KEPASTIAN HUKUM PEMEGANG SERTIPIKAT HAK PAKAI ATAS TANAH NEGARA TERHADAP PEMEGANG SURAT KETERANGAN GANTI RUGI DALAM GUGATAN PERDATA - Jasril Jasril; Indra Afrita; Yeni Triana (Yustitia, 2025)
The human need for land today is increasing. This is due to the increasing number of population, while on the other hand, the land area does not increase. For this reason, the rights and authorities of the parties are regulated in the Basic Agrarian Law (UUPA) Number 5 of 1960. This study is a normative legal research that aims to (1) Analyze the legal arrangements for holders of state land use right certificates against SKGR according to the provisions of Indonesian civil law; (2) Analyze the legal certainty for the holder of the right to use the certificate on state land against the holder of the SKGR in a Civil Lawsuit. This research approach consists of a case approach, a legislative approach, and a conceptual approach. Case Approach based on case analysis of court decision No. 83/PDT. G/2009/PN. PBR, No. 75/PDT. G/2007/PN. PBR, and also decision No. 46/PDT. G/2011/PN. PBR. This study concludes that the legal certainty of the holder of the certificate of right to use state land against the SKGR in a civil lawsuit before the court has powerful legal force based on one of the provisions in Article 16 of the UUPA. The next conclusion is that the legal consequences of the holder of the right to use SKGR state land in a civil lawsuit in front of the court can be measured through the legal arrangement of proof in the civil procedure law.